Funding agencies and disease organizations: Resources and recommendations to facilitate ALS clinical research. Issue 1 (May 2013) - Chad, David A.; Bidichandani, Sanjay; Bruijn, Lucie; Capra, J. Donald; Dickie, Brian; Ferguson, John; Figlewicz, Denise; Forsythe, Melissa; Kaufmann, Petra; Kirshner, Annette; Monti, William
Abstract Ten groups presented their perspectives on facilitating clinical research in ALS including four federal agencies, four disease organizations, one foundation and one advocacy group. The federal agencies (National Institute of Neurological Disorders and Stroke, National Institute of Environmental Health Sciences, Office of Rare Diseases Research, Department of Defense) encourage fostering a team approach between pre-clinical and clinical research investigators, coordinating with patient groups in the early phases of clinical studies, enhancing private and public partnerships, and investigating the interplay between genetic susceptibility and environmental exposure. The disease organizations (Muscular Dystrophy Association, ALS Association, ALS Society of Canada, and the Motor Neurone Disease Association UK) support fellowship training programs to develop ALS clinician scientists, and encourage work on the epidemiology of ALS, on genetic and epigenetic mechanisms that are relevant to ALS pathogenesis, on developing ALS registries and biobanks, and building bridges of collaboration among study groups. The Foundation supports innovative projects, including stem-cell research, and Patient Advocacy is committed to supporting excellence in ALS research and patient care, and believes strongly in enhancing communication between patients and members of the research community.